Limitations On The Application Of Cross-Border Insolvency Principles In Bankruptcy Proceedings In Indonesia: English - Pramesywari, Dania (jurnal.unprimdn.ac.id, 2026)
According to Roman Tomasic, cross-border insolvency, also known as international insolvency, occurs when a debtor declared insolvent holds assets in more than one country or has creditors from other countries. The primary goal of cross-border insolvency is efficiency, so that the bankruptcy proceedings can be resolved in a single case, without having to file separate proceedings in every country where the debtor has debts or assets. This phenomenon is becoming increasingly common due to economic globalization and the rise in international trade. However, in Indonesia, regulations regarding cross-border insolvency remain limited and often pose challenges in handling cases involving foreign assets or creditors.